Pemanfaatan Limbah Compact Disk ( CD ) Dalam Kegiatan Ko-lase Untuk Meningkatkan Kemampuan Motorik Halus Anak Usia 5-6 Tahun Di Raudatul Athfal Miftahul Hidayah - Pratiwi, Shelly; Auliya, Siti (LP2M STAI Al-Musaddadiyah Garut, 2024)
This research was motivated by the problem of improving the fine motor skills of +children aged 5-6 years at RA Miftahul Hidayah. This problem can be seen from children who are not yet able to cut and cut simple shapes according to patterns, cannot stick pictures neatly, and do not dare to express themselves by creating art. This research aims to improve children's fine motor skills through collage activities at RA Miftahul Hidayah by: 1). Describe the fine motor skills of children aged 5-6 years at RA Miftahul Hidayah before carrying out collage activities using waste compact disks. 2) Describe the implementation of collage activities using waste compact disks at RA Miftahul Hidayah. 3) Describe the fine motor skills of children aged 5-6 years at RA Iftahul Hidayah after carrying out collage activities using waste compact disks. The method taken is the classroom action research (PTK) method using the Kemmis MC and Taggart model, with a qualitative approach. Data collection takes the form of interviews, observation and documentation. The results of the research were carried out in 2 meetings, in cycle I the average score was 52.8 with a completion percentage of 65% from 20 children. Meanwhile, in cycle II the average score was 60.9 with a completion percentage of 90% from 20 children. This shows that there was an increase in the average value of children's fine motor development from cycle I to cycle II. Keywords: Collage, Compact Disk Waste, Fine Motor